Optimum system reliability of radial distribution systems with tie lines - Tarnate, Wilbert Rey D. (2011)
Distribution system reliability may be improved by service restoration using tie lines. Restoration via tie-lines takes advantage of alternative sources, thereby reducing the duration of interruptions. In this paper, we used Genetic Algorithm to optimize the reliability of multiple radial distribution systems by determining the optimal number and locations of fuses, reclosers, circuit breakers, normally-closed switches, and tie lines in it. An unbalanced three-phase load flow algorithm was used to check for voltage and loading violations. We quantified the reliability of distribution systems using a composite index comprising weighted reliability indices (SAFI, SAIDI, EENS, ASIFI, ASIDI, and MAIFIE) and protective and switching device costs. In the methodology we used, reliability evaluation considered the response of the protection system, restoration by isolation of faulted segments through normally-closed switches, and restoration through normally-open tie lines. In reliability optimization, past research did not maximize the number or load of customers restored through tie lines while taking into account voltage and loading violations. Our analysis on test systems, however, showed that this factor is significant in determining the optimal location of the devices. In this paper, we considered maximizing the number or load of customers restored.
Undergraduate student project (B.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric power distribution -- Reliability; Radial distribution systems